2010
DOI: 10.1371/journal.pone.0015174
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Application of High Fluid Shear to Chondrocytes Recapitulates Gene Expression Profiles Associated with Osteoarthritis

Abstract: BackgroundExcessive mechanical loading of articular cartilage producing hydrostatic stress, tensile strain and fluid flow leads to irreversible cartilage erosion and osteoarthritic (OA) disease. Since application of high fluid shear to chondrocytes recapitulates some of the earmarks of OA, we aimed to screen the gene expression profiles of shear-activated chondrocytes and assess potential similarities with OA chondrocytes.Methodology/Principal FindingsUsing a cDNA microarray technology, we screened the differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 65 publications
4
46
0
Order By: Relevance
“…Excessive chronic or repetitive mechanical loading of articular cartilage producing hydrostatic stress, tensile strain, and fluid flow (1) has been implicated in the development and progression of OA (2). Indeed, prolonged application of high fluid shear to human chondrocytes in vitro recapitulates gene expression profiles associated with OA in vivo (3). Although OA is classified as a noninflammatory joint disease, the progressive erosion of cartilage involves the action of cytokines and prostaglandins (PGs), which are capable of inducing the expression of matrix-degrading enzymes such as matrix metalloproteinases (MMPs) (4).…”
Section: Osteoarthritis (Oa)mentioning
confidence: 99%
“…Excessive chronic or repetitive mechanical loading of articular cartilage producing hydrostatic stress, tensile strain, and fluid flow (1) has been implicated in the development and progression of OA (2). Indeed, prolonged application of high fluid shear to human chondrocytes in vitro recapitulates gene expression profiles associated with OA in vivo (3). Although OA is classified as a noninflammatory joint disease, the progressive erosion of cartilage involves the action of cytokines and prostaglandins (PGs), which are capable of inducing the expression of matrix-degrading enzymes such as matrix metalloproteinases (MMPs) (4).…”
Section: Osteoarthritis (Oa)mentioning
confidence: 99%
“…According to the results, the described device generated shear stresses spanning over at least four orders of magnitude (0.007-15.4 dyne/cm 2 ). This range of shear stresses started from an extremely low level comparable to interstitial shear stress level (Park et al 2009;Chen et al 2012;Rutkowski and Swartz 2007) to a high level which was deemed to be injurious for chondrocytes (Lee et al 2003; Healy et al 2005;Zhu et al 2010b). It also had a broader scope than previous methods and had the advantage of controlling stimulus intensity in a particular range.…”
Section: Discussionmentioning
confidence: 99%
“…Because water makes up approximately 70-85 % of cartilage weight, accordingly interstitial flow always exists in cartilage tissues undergoing dynamic compression, imparting extremely low shear stress on the cell surface (Rutkowski and Swartz 2007). It has also been reported that the superficial and transitional zones of articular cartilage are remarkably exposed to fluid flow stimulus (Zhu et al 2010b). In addition, fluid flow-induced shear stress is closely relevant with the regulation of articular cartilage metabolism and the pathophysiologic process of articular cartilage (Das et al 1997).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations